2014
DOI: 10.33225/pec/14.58.108
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Confidence in Their Financial Management Abilities: The Role of Socio-Demographic Characteristics and Education

Abstract: The aim of this study was to investigate the impact of gender, age, parent’s education, scholarship and students’ education on students’ confidence in their financial management capability and knowledge. In the research, 259 students participated from two different faculties – the Faculty of Education and the Faculty of Economics. This investigation has revealed that the likelihood of students’ confidence in their financial management capability and knowledge is significantly smaller for students who do not sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Students studying at vocational and business schools had worse financial literacy scores, from 4.3 percentage points to 6.2 percentage points, than students studying at grammar schools. On the contrary, the results of Kozina and Ponikvar (2014) suggested that the likelihood of students' confidence in their financial management capability and knowledge was significantly higher for students that did specialize in economics or business studies.…”
Section: Discussionmentioning
confidence: 85%
“…Students studying at vocational and business schools had worse financial literacy scores, from 4.3 percentage points to 6.2 percentage points, than students studying at grammar schools. On the contrary, the results of Kozina and Ponikvar (2014) suggested that the likelihood of students' confidence in their financial management capability and knowledge was significantly higher for students that did specialize in economics or business studies.…”
Section: Discussionmentioning
confidence: 85%